Application of Problem Based Learning Model to Enhance Student Learning Outcomes Science Elementary School Fifth Grade 145 Pekanbaru - Zaini, Rika Zaini Rika; Alpusari, Mahmud Alpusari Mahmud; H. Lazim N, H. Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The background of this research is the lack of science learning outcomes of students, with an average grade 64.28 while the value of minimum completeness criteria (KKM) IPA is 70. Among the students who totaled 28 people only 11 students who achieve 39 KKM with classical completeness, 28 % . This study is a Class Action Research (CAR), which aimed to improve learning outcomes fifth grade science students of SD Negeri 145 Pekanbaru by applying Problem Based Learning Model. Formulation of the problem: Is the Problem Based Learning Model Application to Improve Student Learning Outcomes Science Elementary School Fifth Grade 145 Pekanbaru?. The research was conducted on the 15th of April to May 9, 2014 with 3 cycles. The subjects were students of class V SD Negeri145 Pekanbaru totaling 28 people who used the data source. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. The survey results revealed the results of student learning on a base score or prior to the application of problem -based learning model , the average student learning outcomes is increased in the daily quiz 64.28 I to 71.07 % . with an increase of 10.56 % in the second daily test increased to 79.1 % with the increase of 23.05 % and the daily test III increased to 89.46 % with an increase of 39.17 %. In Thus, it can be concluded that the model can improve the problem-based learning science learning outcomes elementary School fifth grade students 145 Pekanbaru.Keywords:Problem Based Learning Model, Learning Outcomes